An Assessment of the BGS δDδI Vector Magnetometer - Marsal, Santiago; Torta, Joan Miquel; Riddick, John C. (Polish Academy of Sciences, 2007)
Assuming optimal conditions, the δDδI vector magnetometer can be considered as a semi-absolute instrument. In this paper, the real situation and its differences with the ideal one are critically examined and regarded as potential sources of error. The analysis is applied to the equipment designed by the British Geological Survey (BGS) in the late 1980s, and the given figures are provided from the instrument in use at the Livingston Island Geomagnetic Observatory (LIV). Improved versions have been developed since then, being based on generally the same principles of measurement; thus, most of the results shown can be adapted to the new generation of magnetometers of this type. Peer reviewed